2009
DOI: 10.1159/000218529
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Repair of Complex Vesicouterine Fistula with and without Hysterectomy

Abstract: Objective: To present robotic repair of vesicouterine fistulae (VUF) with and without hysterectomy in 3 cases and to discuss the technique with its outcome. Methods: Three patients were diagnosed with VUF, of whom 2 had a prior history of multiple cesarean sections and 1 had obstructed labor. Preoperative diagnosis of VUF was based on classic history, cystoscopy and imaging studies. All patients underwent pure robotic repair of VUF with hysterectomy in 1 case. The steps of the technique are cystoscopy, bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
0
20
0
2
Order By: Relevance
“…7 Cerrahi onarımda, açık veya laparoskopik yaklaşımlar denenebilmektedir. 8 Bununla birlikte, bazı küçük fistüller spontan iyileşebilmektedir. Fertilite arzusu bulunmayan hastalarda histerektomi de bir tedavi seçeneği olarak sunulabilmektedir.…”
Section: Vezikouterin Fistül Onarımlarındaunclassified
See 1 more Smart Citation
“…7 Cerrahi onarımda, açık veya laparoskopik yaklaşımlar denenebilmektedir. 8 Bununla birlikte, bazı küçük fistüller spontan iyileşebilmektedir. Fertilite arzusu bulunmayan hastalarda histerektomi de bir tedavi seçeneği olarak sunulabilmektedir.…”
Section: Vezikouterin Fistül Onarımlarındaunclassified
“…Ancak, postoperatif "de novo urgency" şikâyetleri olan 2 (%50) hastaya postoperatif dönemde antimuskarinik ilaç başlandı. Ortalama 14,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] aylık izlemlerde hiçbir hastada nüks saptanmadı.…”
Section: Bulgularunclassified
“…[46] Hemal and coworkers presented the first report of robotic repair of complex vesicouterine fistula in three patients and established the procedure to be efficacious with or without concurrent robotic hysterectomy. [47] Feasibility studies have found complex ureterovaginal fistulas to be amenable to robotic ureteroneocystostomy with the robot conferring enhanced identification of relevant anatomical structures. [48] …”
Section: Female Urologymentioning
confidence: 99%
“…When compared with previous methods, they UI J [28,29]. Following sharp dissection, the fistulous opening is sutured closed and omentum is interposed between the uterus and bladder for adequate healing, followed by 3 weeks of Foley catheter drainage [28,29].…”
Section: Management Of a Vufmentioning
confidence: 99%